1993
DOI: 10.1200/jco.1993.11.6.1024
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of patients treated with COMP or LSA2L2 therapy for childhood non-Hodgkin's lymphoma: a report of CCG-551 from the Childrens Cancer Group.

Abstract: Treatment success can be expected in 84% of pediatric patients with localized non-Hodgkin's lymphoma. For patients with disseminated disease, treatment success can be expected in 64% of those with lymphoblastic and 50% of those with undifferentiated or large-cell disease. To date, late adverse events are rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(92 citation statements)
references
References 16 publications
3
88
1
Order By: Relevance
“…Prospective studies conducted in Europe and the United States in the late 1980s demonstrated the importance of agents such as HD-MTX, cyclophosphamide or ifosfamide, and high-dose cytarabine in the management of this malignancy. [1][2][3][4][5][6][7][8][9][15][16][17][18] These studies also contributed to the identification of additional risk factors, such as tumor burden, resection status, and serum LDH levels, that, along with disease stage, had an impact on prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective studies conducted in Europe and the United States in the late 1980s demonstrated the importance of agents such as HD-MTX, cyclophosphamide or ifosfamide, and high-dose cytarabine in the management of this malignancy. [1][2][3][4][5][6][7][8][9][15][16][17][18] These studies also contributed to the identification of additional risk factors, such as tumor burden, resection status, and serum LDH levels, that, along with disease stage, had an impact on prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The major advances in this area have been made using short, high-dose intensity chemotherapy regimens. Initial studies conducted within the Children's Cancer Group (CCG) by Anderson et al 1,2 demonstrated that the 4-drug regimen COMP (cyclophosphamide, vincristine, methotrexate, and prednisone) was significantly more effective than the 10-drug regimen LSA2-L2 (cyclosphosphamide, vincristine, methotrexate, daunorubicin cerubidine, prednisone, cytarabine, thioguanine, asparaginase, hydroxyurea, and carmustine). Subsequently, the CCG demonstrated the efficacy of the CHOP regimen in obtaining high complete response (CR) rates 3 and improved on this strategy with the development of the 'Orange' regimen, 4 while pediatric hematology and oncology groups in Europe were also gradually achieving improved results using short, high-dose intensity regimens.…”
mentioning
confidence: 99%
“…Their first study, CCG-551, evaluated two different treatment regimens, LSA 2 L 2 (cyclophosphamide, vincristine, methotrexate, daunomycin, prednisone, cytarabine, thioguanine, asparaginase, methotrexate, carmustine) or COMP (cyclophosphamide, vincristine, methotrexate, prednisone), for the treatment of childhood NHL. Children with non-lymphoblastic histology demonstrated an improved outcome when treated with COMP compared to LSA 2 L 2 , with a disease-free survival of 50% and 29% respectively (Anderson et al, 1993). Their next study investigated the addition of anthracyclines; specifically, the efficacy of COMP versus daunorubicin plus COMP (D-COMP) in children without bone marrow or CNS involvement.…”
Section: Children's Cancer Groupmentioning
confidence: 99%
“…24,25 Stem cell transplantation for childhood NHL In children with relapsed or refractory NHL, the prognosis is not as promising and the best treatment approach for this poor risk group continues to be a challenge. [26][27][28] Aggressive chemotherapy followed by autologous BMT has been used with some improvement in survival. [29][30][31][32][33] Some centers have investigated AlloSCT in pediatric patients with relapsed/ refractory NHL.…”
Section: Nhlmentioning
confidence: 99%